Investigating the effect of 1,25 dihydroxycholecalciferol-glycosides and phytogenic antioxidants against bacterial chondronecrosis induced by aerosol transmission model - Khawla Alharbi; Andi Asnayanti; Amer Hasan; Wesley J. Vaught; Kathrin Buehler; Jan Dirk Van der Klis; Javier Gonzalez; Michael T. Kidd; Adnan Alrubaye (Journal of Applied Poultry Research)
SUMMARY: Bacterial chondronecrosis with osteomyelitis (BCO) lameness has been a major concern in the broiler industry, causing financial losses and animal welfare issues. BCO lameness is caused by a bacterial infection in leg bones. Pathogens enter the bloodstream via respiratory and intestinal epithelial translocation and infect the tibia and femoral heads of the birds. Supplementation of 1,25(OH)2D3 is crucial in regulating calcium and phosphorus homeostasis, immune system, and bone metabolism. 1,25(OH)2D3 glycosides derived from Solanum glaucophyllum (G-1,25(OH)2D3) were hypothesized to mitigate BCO lameness in broilers. In this study, G-1,25(OH)2D3 alone or in combination with phytogenic antioxidants were tested for their impacts on cumulative BCO lameness in the broiler population. BCO seeder group and the negative control had developed 78,0% and 73.5% cumulative lameness (P = 0.64), respectively. Supplementation of 1 µg/kg of G-1,25(OH)2D3 was more effective in reducing the cumulative lameness than 10 µg/kg of G-1,25(OH)2D3 (P < 0.05). There were no significant differences between 1 µg/kg of G-1,25(OH)2D3 alone or in combination with 500 mg/kg of a mixture of Curcuma longa plus Trachyspermum ammi (PH1), 750 mg/kg of a mixture of Solanum xanthacarpum plus Piper longum (PH2), or 500 mg/kg thyme oil. Therefore, 1 µg/kg of G-1,25(OH)2D3 provided better protection against BCO lameness compared to 10 µg/kg of G-1,25(OH)2D3. Additionally, the combination with phytogenic antioxidants did not result in any further reduction of cumulative BCO lameness compared to the use of G-1,25(OH)2D3 alone.